2022
DOI: 10.1093/deafed/enab042
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported Stress and Child Behavior for 4-Year-Old Children with Unilateral or Mild Bilateral Hearing Loss

Abstract: Children with unilateral or mild bilateral hearing loss are increasingly identified in early childhood. Relatively little is known about how hearing loss affects their developmental trajectory or whether it contributes to parenting stress for these parents. This study aimed to examine child behavior and parenting stress in parents of children with unilateral/mild bilateral hearing loss compared to children with typical hearing. This prospective study involved 54 children with unilateral/mild bilateral hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…According to these studies [ 7 , 8 , 9 , 10 , 11 ] factors that contribute to parenting stress in parents of deaf children include age at diagnosis, degrees of hearing loss, language abilities, mode of communication (spoken language or sign language), child behavior problems, perceived social support, cochlear implants, additional disability with poorer language skills, or higher rates of behavior problems [ 6 ]. Conversely, other studies have not found higher levels of stress among parents of deaf or hard-of-hearing children [ 33 , 34 , 35 , 36 , 37 , 38 ]. According to Dammeyer et al [ 34 ], it is not the hearing loss itself but child-related characteristics, such as additional disabilities and behavioral, emotional, and social difficulties, that negatively impact parenting stress.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…According to these studies [ 7 , 8 , 9 , 10 , 11 ] factors that contribute to parenting stress in parents of deaf children include age at diagnosis, degrees of hearing loss, language abilities, mode of communication (spoken language or sign language), child behavior problems, perceived social support, cochlear implants, additional disability with poorer language skills, or higher rates of behavior problems [ 6 ]. Conversely, other studies have not found higher levels of stress among parents of deaf or hard-of-hearing children [ 33 , 34 , 35 , 36 , 37 , 38 ]. According to Dammeyer et al [ 34 ], it is not the hearing loss itself but child-related characteristics, such as additional disabilities and behavioral, emotional, and social difficulties, that negatively impact parenting stress.…”
Section: Discussionmentioning
confidence: 79%
“…According to Dammeyer et al [ 34 ], it is not the hearing loss itself but child-related characteristics, such as additional disabilities and behavioral, emotional, and social difficulties, that negatively impact parenting stress. Fitzpatrick et al [ 33 ] found that parents of children identified early with unilateral and mild bilateral hearing loss and normal performance in multiple domains including language and behavior, did not report higher stress levels than parents of children with typical hearing [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as the management of pediatric UHL continues to evolve, it is important to recognize the significant emotional strain experienced by parents and caregivers as they attempt to gain access to and navigate care options for their child [11,86]. Recent studies have explored barriers to care access for pediatric patients with UHL and have highlighted inadequate screening tools which delay timelines to interventions, and financial barriers as the primary obstacles to care access [87,88].…”
Section: Barriers To Carementioning
confidence: 99%
“…Furthermore, parents are asked to navigate a confusing breadth of services and potential treatment options available for their child with UHL, ranging from school modifications, hearing amplification, contralateral routing of signal hearing aids, various bone-conduction hearing device options, to surgical placement of cochlear implants. In this process, caregivers often experience frustration with the lack of concrete guidance and often carry a significant level of guilt as they navigate the decision-making process [86,89,90 ▪▪ ]. The ambiguity in treatment guidelines for UHL can leave parents wondering if the severity of hearing loss in their child is significant enough to warrant intervention, or if they have made the best decision for their child's development [89,90 ▪▪ ].…”
Section: Impact Of Unilateral Hearing Loss In Childhoodmentioning
confidence: 99%
“…First, studies often combine MBHL, unilateral hearing loss, and high-frequency hearing loss, as they all fall under the umbrella term of “minimal hearing loss”. ( Fitzpatrick et al, 2010 , 2014 , 2015 , 2022 ; Fitzpatrick, Cologrosso, et al, 2019 ; Laugen et al, 2017 ). Second, mild HL classification often necessitates only the involvement of the better ear, potentially resulting in the categorization of asymmetric hearing loss ( Fitzpatrick et al, 2010 , 2014 , 2015 , 2022 ; Fitzpatrick, Cologrosso, et al, 2019 ; Laugen et al, 2017 ; Vohr et al, 2012 ; Walker et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%